2012
DOI: 10.1101/gr.130161.111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dynamic transcriptome analysis (cDTA) reveals mutual feedback between mRNA synthesis and degradation

Abstract: To monitor eukaryotic mRNA metabolism, we developed comparative dynamic transcriptome analysis (cDTA). cDTA provides absolute rates of mRNA synthesis and decay in Saccharomyces cerevisiae (Sc) cells with the use of Schizosaccharomyces pombe (Sp) as an internal standard. cDTA uses nonperturbing metabolic labeling that supersedes conventional methods for mRNA turnover analysis. cDTA reveals that Sc and Sp transcripts that encode orthologous proteins have similar synthesis rates, whereas decay rates are fivefold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
377
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(407 citation statements)
references
References 48 publications
26
377
1
Order By: Relevance
“…As expected, new transcription was necessary to obtain 4TU-labeled RNA: preincubation with the general transcription inhibitor thiolutin, which has been shown to decrease transcription in N. crassa (Hoyt et al 2000;Lee et al 2009), severely reduced 4TU incorporation, as did chilling cells on ice ( Figure S3, C and D). Incorporation of 4TU into RNA rapidly diminished when excess uracil was added to cultures ( Figure S3E) and 4TU itself had minimal impact on N. crassa growth under the experimental conditions used (,30 min incubation) or during growth for extended periods ( Figure S3F), similar to its minimal effects on growth in S. cerevisiae (Munchel et al 2011) and S. pombe (Sun et al 2012). Furthermore, purified 4TU RNA, unlabeled total RNA and unlabeled poly(A) mRNA programmed the synthesis of [ 35 S]Met-labeled polypeptides with similar distributions of masses in N. crassa cell-free translation extracts ( Figure S3G).…”
Section: N Crassa Nmd Mutations Increase the Levels And Stability Ofmentioning
confidence: 59%
“…As expected, new transcription was necessary to obtain 4TU-labeled RNA: preincubation with the general transcription inhibitor thiolutin, which has been shown to decrease transcription in N. crassa (Hoyt et al 2000;Lee et al 2009), severely reduced 4TU incorporation, as did chilling cells on ice ( Figure S3, C and D). Incorporation of 4TU into RNA rapidly diminished when excess uracil was added to cultures ( Figure S3E) and 4TU itself had minimal impact on N. crassa growth under the experimental conditions used (,30 min incubation) or during growth for extended periods ( Figure S3F), similar to its minimal effects on growth in S. cerevisiae (Munchel et al 2011) and S. pombe (Sun et al 2012). Furthermore, purified 4TU RNA, unlabeled total RNA and unlabeled poly(A) mRNA programmed the synthesis of [ 35 S]Met-labeled polypeptides with similar distributions of masses in N. crassa cell-free translation extracts ( Figure S3G).…”
Section: N Crassa Nmd Mutations Increase the Levels And Stability Ofmentioning
confidence: 59%
“…Genome-wide expression studies in yeast have shown that mRNA synthesis and decay are mechanistically and functionally coordinated, thus supporting the existence of common molecular effectors [6][7][8][9] . In particular, the CCR4-NOT deadenylation complex was first described as a transcriptional regulator and has been implicated in initiation and elongation by RNA polymerase II 10,11 .…”
mentioning
confidence: 94%
“…Recent research suggests that RNA turnover is tightly connected to transcription and that mRNA degradation factors influence the rate of transcription and vice versa (Sun et al 2012(Sun et al , 2013Haimovich et al 2013;Braun and Young 2014). Particularly, Xrn1p appears to play an important role in "buffering" mRNA levels by decreasing the transcription rate, for example, when mRNA degradation rates are slowed (Sun et al 2013;Medina et al 2014).…”
Section: Introductionmentioning
confidence: 99%